The implications of the Lyons report into local government in England for structural reform in Australian local government - Grant, Bligh; Crase, Lin; Dollery, Brian (2009)
The Lyons Inquiry into English local government presented its Final Report in 2007. It has significant implications for local government jurisdictions beyond England. This article considers the import of the Lyons Inquiry for reform to Australian local government. It is argued that the Lyons Inquiry adds weight to other work that questions the traditional reliance on amalgamation as the chief instrument of Australian local government reform. In particular, the "place-shaping" thesis developed in the Lyons Inquiry shows that the Australian emphasis on structural reform has been misdirected. Further, the Lyons Report offers a range of policy options besides municipal amalgamation. - Reproduced.
Keywords: Local government